Lale Devri Bestekarları - Kopuz, Arzu (Sosyal Bilimler Enstitüsü, 1996)
Bazı müzikologlarımız Türk Mûsikisi'ni dönemlere ayırarak tasnif ederken, çeşitli yüzyıllarda yaşamış olan bestekârların kullandıkları form, makam ve usûl tercihlerini baz olarak almışlardır.Bestekârlar meydana getirdikleri kompozisyonlarıyla adeta yaşadıkları asrı simgelemişlerdir. Sanatın hemen hemen bütün kollarında büyük bir atılım yapılmış olan Lâle Devri'nden, Türk Mûsikisi sanatı da nasibini almıştır. Bu araştırmanın Giriş ve özellikle İkinci Bölümünde, Osmanlı İmparatorluğu'nda önemli bir dönem olarak kabul edilen Lâle Devri hakkında genel bilgiler verildikten sonra, diğer bölümlerde sözkonusu devirde yaşamış olan 47 bestekârın hayatı ve ulaşılabilinen eserlerinden bazı örnekler sunulmuştur. Çalışmanın Sonuç bölümünde ise, Lâle Devri'nde eser vermiş musikişinasların besteleri incelenerek, dönemi adeta karakterize eden tespitler, maddeler halinde sunulmuştur.

The Ottoman Empire had changed from the establishment to the Republich of Turkey both art and music. Social, golitical matters and economy and the other subjects changed too. "Tulip Period" in Turkish "Lale Devri" is the best and coloured and the bright revolution of the Ottoman Empire. It was between the 1718 and 1730. Turkish Historians said that Tulip Period was the beginning from the Pasarofça Pact in 1718 to the deth-ro-ne of the ni.Ahmet in 1730. In this period the high society of the Ottoman Empire changed their mind. At the beginning they were religious and fighter, but than they became musicians. They were interested in mysticism and becamu sufi, they read a lot and fond of litera-ture. They wanted to lead a gay life. In this period IILAhmet was thi Empire and the pieceful Nevşehirli Ibrahim Pasha was the vizier of the Ottoman Empire. İbrahim Pasha was married with the empire's daughter. He was the sun-in-low of the empire. They were very good friends. They changed the old political ideas. They were pieceful. They did their best for their country and their people the Ottomans had nearly Europhen look. The first characteristic of the Tulip Period was the liberty of art. The people made fun of music. They had amused themselves with music. Ottomans were living in piece. They were far from war. They had fun. During the "Tulip Period" Ottomans build a lot of Palaces in Istanbul and in the big cities of the countries like Edirne, Konya, Bursa and in the others. They are our important historical master pieces now they build villas and fountains. Put the big parks in order. Resined beautiful gardens in Istanbul - Kağıthane Stream became very papular place because of its position and the picnic places. There were a lot of trees there. Kağıthane was the place of amusement. "Tulip" was the symbol of this periot. There were a lot of tulip gardens in Istanbul. The Palaces were full of tulips. They were white, red. Yellow, orange tulips. Everybody has grouwn tulips both aristocrats and also the commen people. Tulip bulbs were very expensive. Tulip entertain mets were the best characteristic of the Tulip Period. People enjoyed being together, v singing songs, playing Turkish ensturements. They had a good time. The head of the state and the goverment men were fond of music in the summer places, in Sadabat, in the pavilions like Şerefabat, Hüsrevabat, Neşetabat and Çıragan Plase and in Tersane gardents. Musicians, composers, poets and writers were coming together, playing ensturements, singing song. Sailing in Kağıthane Sream. They created a lot of new melodies. Composed many songs. Music and art were all around them. In the summer people were organizing fun tours in "lalezars" and in povilions during the day or at night or in the winter. They were preparing a kind of Turkish sweetmeat, eating, singing and talking and tasting the music. They were leading a guy life. They were spending lot of money, building new houses, villas in the gardens of their houses. They were wasting much money. So the Ottomans and paid more tax than before. High taxes were bad for Ottomans. Poor and the tradesmen weren't pleased. They became poor. This period wesn't only the fun time. There were some good working during the this period. Some entellectuals went to Europe. Suitable European sytles had adapted to the Ottomans. Hand workings improved rapidly. "Tulip Period" was the stage of the development for music, poem and the culture. They build printing offices so a lot of poems and books printed. Twenty-eight Çelebi Mehmet Efendi and his son Sait Efendi were clever men. They went to France as the ambassodors. Çelebi Mehmet was interested in printing. He studied on press. He examined a lot of things in Paris. He was avare of the advantage of the press for his country. When he came back to Turkey, vizier İbrahim Pasha helped him and he build printing offices in Istanbul getting a permission from the "Şeyhülislam". It's name was İbrahim Müteferrika Press. It was the most important thing for Turks. Books became cheap. Everybody bought books easly. In 1729 "Vankulu Dictionary" was the first press, than they pressed a lot of books about the different subjects like history books, geography books and literature books or poems. Before pressing they became chep. Books helped the development of the Ottoman Empire. Bridgroom İbrahim Pasha and his group translated a lot of books into Turkish. We know that Tulip Period influenced our literature. During the period in.Ahmet was the Ottoman Empire. He was a poet. He wrote poems signing Necip. Nevşehirli İbrahim Pasha was the bridegroom of the III. Ahmet. He wrote pyric poems. Poets wrote wonderful qoems, musicians composed vi their best clasical songs. In 1724 Osmanzade Taib became very famous when the empire's child İbrahim was born. He was called "Reis-i Şairan". It means he was the best poet of the Ottoman Empire. There were many fomous litterateurs like Kamil (1723), Nazım (read 1727), Rasih (de.1731), Vahit ( ? ), Mahtumi (de.1732), Arpaeminzade Sami (de. 1733), İzzet Ali Pasha (de. 1735), Seyit Vehbi (de. 1737), Atıf Efendi (de. 1742), Mirzazade Salim (de. 1743), Neyli Ahmet (de. 1748). Nedim was the symbol poet of this period. He wrote a book, it's name is "Divan". Nedim died in 1730. We can find everyting about the Tulip Period in Divan. He wrote about the buildings, about the beautiful places in Istanbul. He wrote about the different parts of Istanbul like Kağıthane, Atmeydani, Eyüp, Tophane and Üsküdar. In the summer whene did the men go, what did thy do, how did they enjoy themselves. In Sadabat, where did they sail, where were the picnic places, what did they do in Nevruz. Nevruz is still the sping bayram in Turkey. What the Ottomans do in the winter, both during the night and at night. How do they prepare sweetmeat and what do they do at that time. They were the topics of the rich Ottoman literature. Fine Arts and Hand Making were very important in "Tulip Period". Bridegroom İbrahim Pasha was interested in art, hand making and architecture. He helped the men and gave them money who were interested in them. Ottomans found new styles in arahifecture. They have taken barok style to Ottomans but they changed it in order to their living. It became different and interesting one. In this period instead of the mosques and monumental building they build pavilions, villas, public fountains, places and civil buildings. First they were using clasical forms but than the buildings were very luxury. They were decorated with the coloured porcelains and the different materials. They used a new sytle in decoration. There were widespread motives an them. "Fruit Room" was the first work in Tulip Period. It is in Topkapi Place. It was full of life. It was full of vases, they were Rull of flowers and fruits. Colour's, flowers, fruits, vitality were the style of Tulip Period. III.Ahmet fountain which is in Üsküdar is the best monument building. It was build by architect Mehmet Ağa. We can see some motives on it. These motives look like the motives in Topkapi Place. They are on marbles. In Istanbul there are a lot of fountains like III.Ahmet Fountain, Tophane fountain (build in 1732), Azapkapi Fountain (build in 1733). They are the vii same style. EI. Ahmet Library (build in 1719). It is an important building. You can visit it in the third court yard of Topkapi Place. White marbles used in this building. There are marble stairs both on the right and on the left side. At the top of the stairs, the porch comes. This library was build by Beşir Ağa. Windows and doors were covered with an elephant tooth. It is a private building. '%rahirn Pasha Külliyesi" is in Şehzadebaşı now. It was build in 1720. It is still an important building. It has a lot of buildings in it's garden. These buildings also have characteristics of the Tulip Period. İbrahim Pasha was from Nevşehir, he was born there. There is an important "Külliye" which was build by Pasha and his group. They went to France first. They examined places parks, and gardents in Paris, than they build places, villas, pavilions in Kağıthane an Boğaziçi. Their names are Sadabat, Hüsrevabat, Kasncihan, and Ferahabat - Besides them they build small paper and porcelain workshops and factories. Percelain endustry became important again. Most of the buildings were build by wood. Sometimes they were burning. It was hard to put out the fire. Ottomans build firebrigade. In Turkish we call them "Tulumbacılar". They we volunteers, brave, young meris groub. They were the grandfathers of our firemen. Tulip Period was the long piece time for the Ottomans. They made a lot of reforms in the country. Reform of music, art, architecture, hand making, literature and culture. Tulip was the symbol at the biginning to the end of the period. Patrona Halil rebelled against the government so the Tulip Period ended. It was a big revolation in 1730. Itri was the most important Turkish musician in the 17th. century. The made progres in music. It continued in the 18th. century too. In these centuries composers composed wonderful compositions using their old music knowlidges and the newness together. Old compositions were very good. We are still listening them. Rich and educated men were interested in music or they were helping the musicions. Tulip Period was between the 1730-1754. During this period the Empire ULAhmet and his grand Vizier Nevşehirli Ibrahim Pasha attached importance to music later-during the empire I. Mahmut's period "Enderun" became the first music academy. The musicians were teaching and learning music there. At the end of the 18 the century music progressed in music. The composers composed wonderful clasic compositions. Historians say that Tulip viii Period was the golden music period. At that time both music and art became very popüler quiet and peaceful period was important for music and art. In the Tulip Period Turkish clasical music developed but folk music was on the secondary plan. ni.Selim's time folk musicions were impressed by clasical Rhythms. Folk composers created folk songs using the clasical elements. The last half of the Tulip Period we can find both clasical composers and the folk composers. At the beginning of the 18th. Century important clasical created. These composers were Şeyh Osman Dede, Tanburi Mustafa Çavuş, Ebu Bekir Ağa, Tab'i Mustafa Efendi. In the second part of the century, we can count III. Selim, Mehmet Ağa, and Hacı Sadullah Ağa. We are still listening to the old compositions in our century. Chorus are still singing the old songs, we love them. In this period not only the musicians but there were important poets, litterateurs, miniaturits, architects and the others. Some of their names are İbrahim Hakkı Efendi who was a sufi, Nedim who was a poet, Sadrazam Damad Koca Ragıb Pasha, Şeyh Gaalip Dede, Levni who was an artist. They were the symbol men of that period. Musicologist studied forms on the old compositions old form, old systems, old tunes and harmonies. They put them into a good order. Now we had an idea about this period. Tulip Period was the golden time for the clasical Turkish music. At the beginning and at the second parts of this writing, I searched the "Tulip Period". This period was the best and an important part of the Ottoman empire the order part of my writing I examined the compositions of the Tulip Period composers. Now we know all about the " TULIP PERIOD
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1996
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1996
Keywords: Müzik; Bestekarlar; Lale Devri; Music; Composers; Tulip Period